Gender differentials in skill use and skill formation in the aftermath of vocational training - Fahr, Rene; Sunde, Uwe (Applied Economics Letters)

Modeling the Impact of Corporate Reputation on Customer Satisfaction and Loyalty Using Partial Least Squares - Helm, Sabrina; Eggert, Andreas; Garnefeld, Ina (Handbook of Partial Least Squares)

Triggers of HR outsourcing decisions--an empirical analysis of German firms - Alewell, Dorothea; Hauff, Sven; Thommes, Kirsten; Weiland, Katrin (The International Journal of Human Resource Management)

Paderborner Forschungs- und Entwicklungswerkstatt - Forschungsfragen und -konzepte der beruflichen Bildung

Bildungsperspektiven in alternden Gesellschaften

Praxisphasen in beruflichen Entwicklungsprozessen - Kremer, H.-Hugo; Tramm, T.; Siemon, J. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Schülerbetriebspraktikum im Übergangssystem - Relevanz, Potenziale und Gestaltungsanforderungen - Kremer, H.-Hugo; Gockel, C. (bwp@ Ausgabe 17, Praxisphasen in beruflichen Entwicklungsprozessen)

Guest Editorial to the Special Section on MODELS 2007 - Engels, Gregor (Software & Systems Modeling)

Modellbasiertes Testen auf Basis des fundamentalen Testprozesses - Spijkerman, Michael; Eckardt, Tobias (Softwaretechnik-Trends)

A Holistic Software Engineering Method for Service-Oriented Application Landscape Development - Sauer, Stefan; Engels, Gregor; Willkomm, Johannes; Baumann, Andrea; Hofmann, Alexander (Advances in Enterprise Engineering II)

Design for Future – Legacy-Probleme von morgen vermeidbar? - Engels, Gregor; Goedicke, Michael; Goltz, Ursula; Rausch, Andreas; Reussner, Ralf (Informatik-Spektrum)

Modelling the Impact of Corporate Reputation on Customer Satisfaction and Loyalty Using PLS - Helm, S; Eggert, A; Garnefeld, I (Handbook of Partial Least Squares - Concepts, Methods and Applications)

Inductively coupled plasma reactive ion etching of bulk ZnO single crystal and molecular beam epitaxy grown ZnO films - Mehta, M.; Ruth, M.; Piegdon, K. A.; Krix, D.; Nienhaus, H.; Meier, Cedrik (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures)

Electron energy structure of self-assembled In(Ga)As nanostructures probed by capacitance-voltage spectroscopy and one-dimensional numerical simulation - Lei, Wen; Notthoff, Christian; Offer, Matthias; Meier, Cedrik; Lorke, Axel; Jagadish, Chennupati; Wieck, Andreas D. (Journal of Materials Research)

Ultrathin K∕p-Si(001) Schottky diodes as detectors of chemically generated hot charge carriers - Huba, K.; Krix, D.; Meier, Cedrik; Nienhaus, H. (Journal of Vacuum Science & Technology A: Vacuum, Surfaces, and Films)

Kontextsensitive Qualitätsplanung von Softwaremodellen - Voigt, Hendrik
The Model Quality Plan (MQP) approach provided by us allows for the systematic and efficient development of quality plans that serve as a basis for the assessment of software models. MQP emphasizes the context of a software model as a major factor of influence for the whole quality planning activity. In order to adjust a quality plan to project specific requirements, quality goals are derived from a characterization of that context. We achieve a differentiated description of quality goals by introducing structured goals and questions in combination with a defined quality model. Afterwards, metrics and indicators are identified for checking the fulfillment of the quality goals. The result of our approach consists of a context sensitive quality plan for software models. Conceptually, we combine a metamodel for formulating relevant contents, a process that serves as a guideline for defining quality plans, and a rule concept for packaging and reusing experience into an integrated framework. We show its feasibility by three case studies that include a quality plan for analysis models, design models, and test models, respectively. For that, we provide tool support for the definition and application of quality plans.

Platform independent modeling of synthesizable software systems using UML 2 - Schattkowsky, Tim

Pattern based business process design and verification - Förster, Alexander

Model-based evaluation of service-oriented enterprise architectures - Assmann, Martin
Enterprise Architecture (EA) has undergone many changes since the IT has found its way into the world of enterprises. The introduction of Service-Oriented Architecture (SOA) is such a change with major consequences. The introduction of an SOA increases the flexibility and thus the productivity of an enterprise architecture, but unfortunately also its complexity. This makes the transformation of an enterprise architecture to an SOA-like enterprise architecture to a challenging and risky task. To overcome the change- and complexity-related problems when introducing SOA, Enterprise Architecture Management (EAM) systems are required. The approach of this thesis suggests a method on how to establish Enterprise Architecture Management that is especially suited for an SOA introduction. This thesis suggests a variant of an EAM system that is especially suited for the introduction of an SOA. The presented method on creating such an EAM system includes guidance on how to define a meta model for Service-Oriented Enterprise Architecture (SOEA), which is harmonized with the respective enterprise architecture. The SOA introduction is especially supported by defining SOA quality criteria and corresponding metrics. Some metrics have to be ascertained by experts. Other metrics have their measuring points within the SOEA models (instances of the SOEA meta model) and their calculation is automatable. Creating and maintaining SOEA models as well as applying the automatable metrics are supported by an eclipse-based tool. As metrics only produce measures that are hard to interpret, indicators are introduced. They allow interpreting the measures concerning the quality criteria. With the help of this EAM system, the transformation of an enterprise to a service-oriented enterprise can be planned and the level of goal-achievement (SOA-conformance of the EA) can be monitored steadily. By this, the contribution of this work aims at the reduction of the risk when introducing an SOA.

Innovation and Reform in College-based VET Contexts: An outline of research in England and Germany - Ertl, H.; Kremer, H.-Hugo (SKOPE)